Construyendo el género más allá de la nación: dimensión nacional e internacional de la movilización de las mujeres antifascistas (1934-1950) - Mercedes Yusta (Mélanges de la Casa de Velázquez)
This paper analyses the strategies and genderised discourses that anti-fascist women used in the course of their political action nationally and internationally, from the 1930s until the beginning of the Cold War. To that end the author has examined two women’s organisations, one national—the Unión de Mujeres Españolas—and the other international—the Women’s International Democratic Federation. An examination of the two organisations shows that action by anti-fascist women operated at two levels: nationally, with women acceding to citizenship in much of Europe, and internationally with these women seeking to influence the reconstruction of post-war Europe. To legitimise their action at either level, these organisations built up complex identities, ranging from a universal gender model based on maternity values to the use of nationalist imagery as a means of mobilising women.